Analysis of factors affecting intention to purchase buffalo milk and milk products among Malaysian consumers - Rosiman, Nurul Hidayah; Ungku Zainal Abidin, Ungku Fatimah; Meor Hussin, Anis Shobirin (Human Resources Management Academic Research Society (HRMARS), 2024)
Buffalo milk has many health benefits, such as reducing the risk of cardiovascular diseases and cancer and improving bone mass. However, the buffalo milk market sector in Malaysia can be considered relatively young as the products availability are still limited. Although Malaysia's dairy market has increased positively in the past years, limited research was reported on the factors that influenced the purchase intention among Malaysian consumers for buffalo milk and buffalo milk products. This study investigates factors that influenced consumer demands towards buffalo milk and buffalo milk products, including consumer awareness), trust, knowledge, attitude, subjective norms, perceived behavioral control (PBC), acceptance, and purchase intention. This study adopted the extended Theory of Planned Behaviour (TPB) model, which tested the influence of awareness, trust, acceptance, and knowledge on consumers' intention to purchase buffalo milk and buffalo milk products. A total of 202 usable data were collected from consumers using self-administered surveys. Data obtained from the survey were then analyzed using SPSS (version 22) and Smart PLS. The results indicated that PBC (p<0.05) and acceptance (p<0.05) have a significant relationship with the purchase intention of buffalo milk and milk products. Knowledge indirectly influences the purchase intention, while it has a significant relationship with acceptance (p<0.05). This study could provide information that help the marketers or dairy industry understand to fulfil the consumers' demand for buffalo milk and milk products consumption in Malaysia.